2006
DOI: 10.1007/s00228-005-0079-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing use of medicines in elderly persons: a five-year follow-up of the Kuopio 75+Study

Abstract: The number of medicines and the prevalence of polypharmacy and excessive polypharmacy increases with advancing age. In order to avoid possible harmful effects and to optimize medication it is necessary to assess the medication regimen at regular intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
1
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 33 publications
12
90
1
3
Order By: Relevance
“…In our study, 43.8% of the sample had bought ! 10 medicines, which is many more than Jyrkkä et al (2006) reported: 28% of old people had used this many medicines. However, unlike such earlier work our study included all different medicines in the last 2 years of life, and not all of these were necessarily used at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 43.8% of the sample had bought ! 10 medicines, which is many more than Jyrkkä et al (2006) reported: 28% of old people had used this many medicines. However, unlike such earlier work our study included all different medicines in the last 2 years of life, and not all of these were necessarily used at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…The number could reflect the total numbers of drugs used in the patient's medication regimen, or it could refer to the number of drugs for a particular condition (15) which is often the case in studies of psychiatric disorders (16,20). Further, in research studies, the number of drugs which are defined as polypharmacy varies from study to study: 2 or more drugs (13,16,21), 3 or more drugs (22), 5 or more drugs (13,14,23,24), 6 drugs (9,25,26), 10 or more drugs (4,27). However, the most common definition is the use of 5 or more drugs (10).…”
Section: Definitionsmentioning
confidence: 99%
“…Studies exploring polypharmacy have been conducted in different clinical settings, in out-patients/ambulatory patients (14,25,(30)(31)(32)(33), hospitalised patients (26,(34)(35)(36), patients in nursing homes (37,38), and elderly patients (25)(26)(27)32,33,39). Studies have also been performed based on data from prescription or population databases (13,28,(40)(41)(42).…”
Section: Frequency Of Polypharmacymentioning
confidence: 99%
See 1 more Smart Citation
“…6 It is estimated that by 2020, more than 50 % of persons living with HIV infection will be aged 50 years or older. 7 Polypharmacy, defined as the concomitant use of multiple medications (e.g., customarily five or more medications), has been associated with increasing age 8,9 and with an increased risk of adverse drug reactions, increased hospitalizations, poor adherence, inappropriate drugs, falls and fractures, and drug-drug interactions. [10][11][12][13][14][15] The risk for drug-drug interactions may be particularly increased among the aging population of HIV-infected adults due to treatments for multiple comorbidities in this population [16][17][18][19] as well as the concomitant use of ARV therapy.…”
Section: Introductionmentioning
confidence: 99%